INTERAKSI SESAMA ORANG TUA ANAK AUTIS DALAM MENGASUH ANAK - Takbirani, Zulfitriana - (Pendidikan Sosiologi, 2014)
Having a child with autism is a difficult time interacting with parents in thecommunity but in SKH YPPA fellow parents of autistic children are able to interact withboth. This study aimed to describe the Social Interaction Fellow Parents of AutisticChildren (Study: Parents in SKH YPPA East Andalas Padang). This type of research usedin this study uses qualitative research and descriptive. Location of the study in SKHYPPA East Andalas Padang. The informants in this study amounted to 15 people includesparents who are in SKH YPPA during the learning process through the study oftechniques of observation, interviews and document study. Accuracy of data is analyzedwith an interactive model that consists of data collection, data reduction, data presentationand conclusion. The theory used is the Symbolic Interaksionesme of Herbet Blumer. Theresults showed that: (1) Profile Parents of Autistic Children those of the upper middlefamilies, have higher education and comes from the city of Padang, (2) cooperationamong parents of children with autism face the behavior of children with autism differentof a normal child. (3) the impact of the interaction between the parents that increase theconfidence of parents, parents of children treated for the better and increased knowledgeof nutrition.